Predictive value of peripheral blood α1‐acid glycoprotein in medical abortion outcomes with mifepristone and relativity of concentration. Issue 1 (13th October 2021) - Li, Fuyao; Shou, Yueyao; Zhu, Ruru; Chen, Xiue; Shi, Beibei
Abstract: Objective: To illustrate the predictive value of peripheral blood α1‐acid glycoprotein (AAG) in abortion outcomes with mifepristone and the relativity of concentration. Methods: A total of 134 patients who met the criteria were enrolled. The AAG and mifepristone concentrations were determined, and Student's t ‐test was used to assess significant differences in the levels of AAG between the complete and incomplete abortion groups. Results: The decrease in AAG concentration was associated with incomplete abortion, whereas the increase in AAG concentration was related to complete abortion ( P  < 0.01). In addition, the concentration of AAG was correlated with the concentration of mifepristone ( r  = 0.7375, P  < 0.001). Conclusion: Our preliminary results suggest that AAG may serve as a biomarker for the prediction of incomplete abortions. Abstract : We found that a low α1‐acid glycoprotein concentration is associated with incomplete abortion and may serve as a biomarker for the prediction of incomplete abortion.